IMPLEMENTASI FUZZY LOGIC UNTUK KUALITAS UDARA, SUHU, DAN KELEMBABAN UDARA BERBASIS IOT - Tamaji, Tamaji; Utama, Yoga Alif Kurnia (Foristek, 2023)
Air is the most important factor in human life. Air quality is the most supportive factor in the development of everyday living things. Temperature, Humidity and PPM (Parts Per Million) substances in the air are the parameters most often found in the environment around where we live. Every day there is and increase in pollution from motorized vehicles without us knowing how bad or good the air condition in our environment is. Therefore we need and air quality monitoring to find out how good the air condition around us is by using the MQ-135 gas sensor which is produces air quality output and using the DHT11 sensor which is output the temperature and humidity of the air around the sensor. And using an ESP8266 microcontroller based to display the output on the sensor anywhere and anytime with internet. It is hoped that this tool can be useful to determine the condition of the room good or bad so that users can improve the condition of the room where they live. It is also hoped that this tool can detect gasses leaks that occur in closed room and provide a warning to the user’s cellphone.